Biochemical characterization and biological action of an haemorrhagine from the bothrops brazili venom - Isla, Martín (2003)
Objective: To characterize a hemorrhagic protein from Bothrops brazili snake venom and to determine if the polyvalent antibotropic serum is able to neutralize it. Material and Methods: A hemorrhagic protein from Bothrops brazili snake venom was purified through two chromatographical steps: Sephadex G-100 and CM Sephadex C-50, respectively, using 0,05M ammonium acetate buffer pH 7. In the last chromatographical system the protein was eluted after 0,3M sodium chloride was applied; thus, a unique band was achieved by PAGE-SDS. A hemorrhagic action monitored through caseinolytic activity obtained 8,4 folds of purification and the minimum hemorrhagic dose (MHD) was 6,61 ug in albine mice. Results: A structural analysis of associated carbohydrates showed 8,05% of hexoses, 11,62% of hexosamines, and 0,69% of sialic acid; its termostability was detected at 50°C for 10 minutes while total inhibition was observed above this. This protein was very unstable at pH 5, 5mM; EDTA, glutamic acid and glutatión had potent inhibitor effects. In contrast, 10mM of Ca+2 increased the hemorrhagic area. Conclusions: Both inmunodiffusion and inmunoelectrophoresis essays showed that polyvalent botropic antivenom (NIH-Lima) recognized the hemorrhagic protein. Furthermore, in vivo experiments showed that the antivenom was capable to neutralize the whole venom but not purified haemorrhagine.